Determinação simultânea de ferro e níquel em suplementos alimentares por HR-CS SS-GF AAS - Adolfo, Franciéle Rovasi (2019)
In this work a method was developed for the simultaneous determination of Fe and Ni as contaminants in dietary supplements by high-resolution continuum source graphite furnace atomic absorption spectrometry and direct solid sample analysis (HR-CS SS-GF AAS). Measurements were done with the secondary lines of Ni and Fe at 352.454 nm and 352.604 nm, respectively, to avoid spectral interferences. The peak volume selected absorbance (PVSA), obtained from the sum of the integrated absorbance values of the center pixel plus the four adjacent ones (CP ± 2) was used as an analytical signal for the quantification of the elements. The best temperatures for pyrolysis and atomization for Fe and Ni were 1000 and 2700 °C, respectively. The use of chemical modifiers was not necessary and no matrix effects were observed. The samples were considered sufficiently homogeneous, since the calculated homogeneity factor was less than 10. Sample mass ranged from 0.25 to 2.8 mg depending on the type of the sample. To compare the measurements performed with different sample masses, the PVSA was normalized for a sample mass of 1 mg. Calibration curves for both analytes were obtained simultaneously, using aqueous standard solutions and standard addition method, for comparison for both calibration modes. The limit of detection was 514 ng g-1 for Fe and 11 ng g-1 for Ni. The precision ranged from 1.33 to 5.57% and from 4.31 to 9.21% for Fe and Ni, respectively. The method accuracy was assessed with recovery experiments and statistical comparison between the analytes concentrations, which were obtained by measurement solid samples with the proposed method and after digestion of the samples. The recoveries ranged from 91.2 to 106.3% for Fe and 75.9 to 111.7% for Ni when the samples were fortified with 5, 7.5 and 10 ng of Fe and 50, 75 and 100 pg of Ni and measured by the proposed method. The proposed methodology was successfully applied to determine both metals in different dietary supplements.